Pengaruh Risiko Likuiditas dan Risiko Kredit serta Efisiensi Bank Terhadap Stabilitas Keuangan Bank pada Bank Konvensional di Indonesia - Jumriana .; Wirasmi Wardhani (CV. ITTC INDONESIA, 2026)
This study aims to analyze the effect of liquidity risk, credit risk, dan bank efficiency on the financial stablitiy of conventional banks in Indonesia. Financial stability of banks is an important aspect in maintaining the sustainability of the financial system and economic growth. This research uses secondary data obtained from the financial statements of conventional bank in Indonesia during the period 2020-2024. The analytical method used in this study is panel data regression with the help of Eviews 12 software. Liquidity risk is measured by Liquidity to Total Assets (LTA), credit risk is measured by Non-Performing Loans (NPL), bank efficiency is measured by the Operating Expense to Operating Income Ratio (BOPO, while financial stability is proxied by the Z-Score. The result show that liquidity risk has a negative and insignificant effect in bank financial stability. Credit risk has a positive but insignificant effect on bank financial stability. Simultaneously, liquidity risk, credit risk, and bank efficiency significantly affect the financial stability of banks. These findings indicate that operational effeciency is an important factor in maintaining bank financial stability. Therefore, bank need to improve operational efficiency and manage liquidity and credit risk more effectively in order to maintain the stability of the financial system.